Implementation of the Problem based Learning Model to Enhance High Order Thinking Skills (HOTS): A Systematic Literature Review - Lingga, Leny Julia; Nusantara, Toto; Mashfufah, Aynin (Journal Of Teaching And Learning In Elementary Education, 2024)
High Order Thinking Skills became the center of attention to achieve the goal, namely that students can think at a high level in any matter, one of which is by using learning models during the teaching and learning process. Therefore, this article discusses an overview of problem based learning and high order thinking skills (HOTS) learning models. This research applies the Systematic Literature Review (SLR) method by collecting data through POP (Publish or Perish) and ERIC. resulting in an initial database of 18,724 articles from ERIC and 116 articles from Scopus. Then the data was filtered based on descriptors with the keyword "thinking skills," resulting in 2,176 articles. Next, data was filtered based on the education level of elementary school students, with a total of 230 articles. Next, the focus was narrowed to five articles for final analysis. Topics studied include education level, year of publication, and analysis results. The relationship between the problem-based learning model and student HOTS is not limited to exact subjects such as mathematics and science. Students are also trained to have high analytical skills in non-exact subjects such as social sciences (IPS), where they are expected to be able to understand large amounts of material effectively.